Microbial decomposition - Tassin, B.; Thevenot, D.R. (Mathematical submodels in water quality systems, 1989)
The authors discuss the role of microbial decomposition in biodegradable processes of organic pollutants, and turns to mathematical models of microbial decomposition. They estimate parameters. Very detailed bibliography. -D.J.Davis